2022
DOI: 10.3390/s22103772
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous Best Integer Equivariant Position Estimation Using Google Pixel 4 Smartphones for Single- and Dual-Frequency, Multi-GNSS Short-Baseline RTK

Abstract: High-precision global navigation satellite system (GNSS) positioning and navigation can be achieved with carrier-phase ambiguity resolution when the integer least squares (ILS) success rate (SR) is high. The users typically prefer the float solution under the scenario of having a low SR, and the ILS solution when the SR is high. The best integer equivariant (BIE) estimator is an alternative solution since it minimizes the mean squared errors (MSEs); hence, it will always be superior to both its float and ILS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A unimodal transformation and a search-and-shrink scheme based on the integer leastsquares (ILS) principle find the optimal ambiguity integers with a real-time computational load [27]. Until recently, the method of best integer equivariance (BIE) has proven to be a better replacement [28], where the AR performance is optimized in the sense of minimizing the mean square error [29][30][31]. However, these methods, including BIE, naturally consider the input float ambiguity estimations to be unbiased integers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A unimodal transformation and a search-and-shrink scheme based on the integer leastsquares (ILS) principle find the optimal ambiguity integers with a real-time computational load [27]. Until recently, the method of best integer equivariance (BIE) has proven to be a better replacement [28], where the AR performance is optimized in the sense of minimizing the mean square error [29][30][31]. However, these methods, including BIE, naturally consider the input float ambiguity estimations to be unbiased integers.…”
Section: Methodsmentioning
confidence: 99%
“…This does not fit in the application of smartphone AR since the existence of IPB, carrier phase multipath effects, and antenna offsets lead to non-negligible ambiguity biases. As a result, the unimodal transformation and the search-and-shrink scheme are inaccurate and likely to produce a set of incorrect ambiguity integers [31]. Although PAR coupled with improved ambiguity validation strategies, such as protection-level, are proposed [32,33], they are generally not sufficiently efficient to identify the correct ambiguity integer set for smartphones due to the volume of such ambiguity biases and the significant measurement noises.…”
Section: Methodsmentioning
confidence: 99%
“…The results indicated that the L5/E5a/B2a signals could generally obtain higher IAR fix-rate and positioning accuracies than the L1/E1/B1 signals. Yong et al [ 35 ] compared the best integer equivariant (BIE) estimator to the integer least squares (ILS) and float contenders using GNSS data collected by Google Pixel 4 smartphones for short-baseline RTK positioning. The results indicated that the BIE estimator will always give a better RTK positioning performance than that of the ILS and float solutions while using both single- and dual-frequency smartphone measurements for the combination of GPS + Galileo + QZSS + BDS.…”
Section: Introductionmentioning
confidence: 99%